Health-related quality of life analysis in ovarian cancer clinical trials involving PARP inhibitors: a critical methodological perspective - Fiteni, Frédéric; Péron, Julien (Quality of Life Research, 2022)
The poly (ADP-ribose) polymerase inhibitors (PARPi) have yielded significant clinical benefits as maintenance therapy in women with newly diagnosed and relapsed platinum-sensitive advanced ovarian cancer. These drugs were approved based on progression-free survival, the primary endpoint of their respective pivotal trials. Health-related quality of life (HRQoL) and/or patient-reported outcomes were included in these trials as a secondary exploratory endpoint. Nevertheless, many weaknesses in the analysis of HRQoL across these trials can be noticed. Heterogeneity and suboptimal HRQoL analysis in oncology trials contribute to misconceptions about this endpoint among oncologists and prevent quality of life as being an endpoint used for approvals. In this article, we discuss these HRQoL results from a methodological perspective and propose some solutions for improvement that could be used by regulatory and academic institutions running ovarian cancers trials. Notably, we suggest to measure and analyze HRQoL data after disease progression, to focus dedicated papers on the statistical analyses of HRQoL recommended by the SISAQOL consortium (linear mixed model for repeated measures and time-to-event approaches) and to communicate on available guidelines to ensure compliance with best international practices regarding the measurement and analysis of HRQoL.